Novel periodic bilayer Au nanostructures for ultrasensitive surface‐enhanced Raman spectroscopy - Wu, Guitai (2020)
The detection of trace molecules is of great significance in many practical applications, and the development of surface‐enhanced Raman spectroscopy (SERS) technique is critical in order to achieve this end. In this work, a novel periodic bilayer Au nanostructure constructed by a porous upper layer and a lower layer of nanoparticle arrays, is fabricated by electron beam lithography (EBL) process for SERS. The repetitive unit is 400 nm × 400 nm, and both diameters of the nanopores of the porous layer and the nanoparticles are ≈200 nm, with ≈10 nm nanogaps between nanopores and nanoparticles. The SERS performances are characterized with Rhodamine 6G (R6G), and compared with that of monolayer Au nanoparticle arrays, the Raman intensity of R6G on bilayer Au nanostructure is ≈12 times stronger, which can be ascribed to a lager electromagnetic field enhancement from the nanogaps. Moreover, the analyzed molecules can be accumulated at the nanogaps due to the special bilayer structure, resulting in stronger Raman signal intensities and a very low detection limit (≈10−13 mol L−1). The novel bilayer nanostructure not only offers an alternative high performance SERS platform for highly quantitative analysis, but also provides another strategy (molecule accumulation) to promote molecule detection.